A study on stryhcnos potatorum and pisum sativum as natural coagulants for meat food processing wastewater - Pahazri, Nor Fadzilah (2018)
Wastewater generated from meat food processing industry has significant effects on the environment. Many methods have been reported for removing turbidity, total suspended solids (TSS), chemical oxygen demand (COD), oil and grease (O&G) and colour from meat food processing wastewater (MFPW). The most common method among them is flocculation-coagulation process which is widely used. Although inorganic coagulants are prominent in wastewater treatments, its application may cause toxic residual. In this study, the attempt has been made to study the performance of S. Potatorum (nirmali) and P. Sativum (pea) seed as natural coagulants in the flocculation process. A further aim is to determine the optimum conditions for the treatment of MFPW effluents such as coagulant dosage, mixing rate and pH. An adsorption study was also carried out to study the adsorption potential of these coagulants to treat MFPW. A lab-scale treatment tank was developed to evaluate the effectiveness in MFPW treatment. Jar test results showed that optimum dosage, pH and mixing rate for S. Potatorum were pH 8 with dosage of 150 mg/L and 150 rpm mixing rate with the removal of turbidity, TSS, COD, O&G and colour are 91%, 97.6%, 58.4%, 79.9% and 84.3% respectively. Meanwhile, for P. Sativum, the optimum condition were observed at pH 8 with dosage of 150 mg/L and 150 rpm mixing rate with the removal of turbidity, TSS, COD, O&G and colour 87.8%, 97.3%, 65.5%, 77.9% and 76.5% respectively. The adsorption study was found that the analysis fitted well to the Langmuir isotherm for both natural coagulants. Results show that the percentage of turbidity, TSS, COD, O&G removal by chemical coagulants are quite similar than natural coagulants when lab-scale treatment tank was used to treat the MFPW. This indicated that these natural coagulants have a potential to use as alternative in wastewater treatment.